Farmers and genebanks: creating alliances to help rural communities cope with climate change - Platform for Agrobiodiversity Research (2011)
The focus of the work was on the needs and concerns of the indigenous communities and their farmers. The emphasis was on creating an environment in which farmers could identify what they felt would be most useful to meet the challenges they faced, knowing that their own traditional knowledge and materials remained under their control.